EFFECTIVENESS OF E-LKPD IN IMPROVING STUDENTS' MATHEMATICAL PROBLEM SOLVING - Thitra Padma Rani; Sugeng Sutiarso; Rangga Firdaus (EDU-MAT: Jurnal Pendidikan Matematika, 2024)
The development of digital learning media as problem-based E-LKPD has become a significant trend in the education sector. This media utilizes information and communication technology to provide students with a more interactive, interesting and relevant learning experience. Nevertheless, it is important to determine the extent of the media's contribution to improving students' mathematical problem-solving abilities. Therefore, this research aimed to determine the effectiveness of PBL-based E-LKPD on flat-sided geometric material to improve the ability to solve mathematical problems. This research is a quasi-experimental research with a pretest-posttest design. The research subjects were class VIII students at SMP Negeri 3 Banjar Baru. Class VIII A is the experimental class and class VIII C is the control class. Each class has 30 students. The research instrument is questions in the form of essays on flat-sided geometric material that includes problem solving skills. The effectiveness of E-LKPD is measured using the N-Gain test. The research results show that the effectiveness of E-LKPD is in the high category. Keywords: Aptitude for problem-solving, E-LKPD, PBL, digital learning